Deliberating with the Autocrats? A Case Study on the Limitations and Potential of Political CSR in a Non-Democratic Context - Anna-Lena Maier; Dirk Ulrich Gilbert (Journal of Business Ethics, 2022)
Extant literature on Political CSR and the role of governments in the governance of business conduct tends to neglect key implications of the political-institutional macro-context for public deliberation. Contextual assumptions often remain rather implicit, leading to the need for a more nuanced, explicit and context-sensitive exploration of the theoretical and practical boundary conditions of Political CSR. In non-democratic political-institutional contexts, political pluralism and participation are limited, and governmental agencies continue to play the most central role in regulation and its enforcement. Drawing on a qualitative case study on a nuclear energy project in the Hashemite Kingdom of Jordan, we show how both governments and MNCs co-create a context hostile to socially responsible business conduct in the sense of Political CSR. Utilizing rich qualitative data derived from interviews, public documents, and participant observation between 2008 and 2018, we specifically illuminate how—through which interactions and strategies—the multiple governmental and corporate actors involved counter civil society demands for public deliberation, indicating the limitations of Political CSR in non-democratic political-institutional contexts. We particularly contribute to the development of Political CSR by analysing the role of coercive and discursive forms of power. We thus offer a more nuanced perspective on the role of governments in constraining the room for public deliberation in the sense of Political CSR.
Keywords: 300; Political CSR; Power; Governments